2018
DOI: 10.1111/apa.14582
|View full text |Cite
|
Sign up to set email alerts
|

Remission of proteinuria in multidrug‐resistant idiopathic nephrotic syndrome following immunoglobulin immunoadsorption

Abstract: Patients with multidrug-resistant idiopathic nephrotic syndrome can be successfully led into remission by IgIA prior to reaching end-stage renal disease. However, IgIA does not suppress the need for heavy additional immunosuppression to control INS in most cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“… 15 A recent retrospective study by Nattes et al. 16 evaluated the efficacy of plasma protein (IA) in 14 children with refractory INS. This study reported a complete and partial remission rate of 64%, but all patients displayed relapse when IA was stopped.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 15 A recent retrospective study by Nattes et al. 16 evaluated the efficacy of plasma protein (IA) in 14 children with refractory INS. This study reported a complete and partial remission rate of 64%, but all patients displayed relapse when IA was stopped.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the available data originate from Japan and relate to patients with low-density lipoprotein (LDL)-apheresis. 12 , 13 , 14 , 15 , 16 …”
mentioning
confidence: 99%
“…All those RNAs, including EBER1 and EBER2 are powerful TLR3 agonists [ 35 ] susceptible to interact with TLR3 expressed on the podocyte and to affect podocyte integrity in a similar way as previously described by Shimada and Garin. Moreover, the transmission of proteinuria to mice by antiUCHL1 IgG antibodies purified from a relapsing patient [ 36 ], as well as the efficacy of immunoglobulin adsorption in the multiresistant forms of INS [ 37 ] are also relevant arguments to involve antibodies as the second podocyte hit that leads to massive proteinuria. It turns out that EBNA1 and UCHL1 share two short peptide sequences located in the immunogen domain of EBNA1 and in close vicinity at the surface of UCHL1 (blast in https://web.expasy.org/sim/ ; reference of protein sequences: YP_401677.1 and NP_004172.2 respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Raina et al reported on 11 steroid/cyclosporine-resistant children with INS where apheresis induced remission in 64%, i.e., proteinuria decreased from 9.7+/−2.5 to 1 +/0.5 g/d [11]. Similarly, Nattes et al [12] gave IA (10 sessions over a 2-week period) to 14 steroid/calcineurin-inhibitor-resistant children with INS (58% were FSGS); this resulted in full or partial remission in 50% and 15% of cases, respectively.…”
Section: Discussionmentioning
confidence: 99%